1997
DOI: 10.1007/s11606-006-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Role Models on Medical Students

Abstract: OBJECTIVE: To explore the relationship between exposure to clinical role models during medical school and the students' choice of clinical field for residency training, and to estimate the strength of this association. DESIGN: Cross-section study.PARTICIPANTS: Of the 146 graduating medical students in the class of 1995, 136 participated. MEASUREMENTS AND MAIN RESULTS:Clinical field chosen by students for residency training and the students' assessment of their exposure to and interaction with physician role mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
146
0
9

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(165 citation statements)
references
References 6 publications
8
146
0
9
Order By: Relevance
“…In addition, several studies have found that role modelling can have a significant impact on medical students' choice of career [13,18,21,29,33], whilst a lack of good role models can also be discouraging [28,30]. Role models apart from personality need to be clinically competent and have teaching ability [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have found that role modelling can have a significant impact on medical students' choice of career [13,18,21,29,33], whilst a lack of good role models can also be discouraging [28,30]. Role models apart from personality need to be clinically competent and have teaching ability [35].…”
Section: Discussionmentioning
confidence: 99%
“…Career information is available in various written and web-based forms [14]. In addition, some students will also turn to their role models [35], whilst careers fairs have recently been found to be highly valued opportunities for students to meet trainees and consultants on a one-to-one basis to see what working in that specialty is really like [15]. It is important that paediatricians do take part in such events especially when students do not encounter paediatrics until the final year and may not until this stage have considered paediatrics as a career option.…”
Section: Careers Informationmentioning
confidence: 99%
“…Unfortunately, most medical faculty members have little formal training in teaching methods (MacDougall & Drummond, 2005;Taylor, Tisdell, & Gusic, 2007). Thus, faculty members often emulate the professional behaviours of their own preceptors and refer to these actions as role modeling (Egnew & Wilson, 2011;Matthews, 2000;Wright, Wong, & Newill, 1997). Sociologist Robert Merton (1968) stated that "the concept of role model can be thought of as more restricted in scope denoting a more limited identification with an individual in only one or a selected few of his roles" (pp.…”
mentioning
confidence: 99%
“…Research in the area of role modeling has primarily focused on the qualities and attributes of exceptional role models, and less attention has been given to the act of role modeling itself (Elzubeir & Rizk, 2001;Jochemsen-van der Leeuw, van Dijk, van Etten-Jamaludin, & Wieringade Waard, 2013;Wright, 1996;Wright, Wong, & Newill, 1997). The distinction between role models and role modeling is blurred, thus exposing a need for a precise definition of what role modeling entails.…”
mentioning
confidence: 99%
See 1 more Smart Citation